Current legal problems of operation rural in Ukraine - Савельева, О. М. (Theory and practice of jurisprudence, 2016)
Problem setting. The last two decades of growing «gap» between urban development and rural areas, which on paper may prove statistics, and for visual proof of this fact is enough to visit a few villages in various regions of our country. The most difficult problems in the countryside among many others is the lack of motivation to work, poverty, labor migration, unemployment, lack of social infrastructure, deepening demographic crisis and the withering away of villages. Recent research and publications analysis. Research on the functioning of public relations in the field of sustainable rural development and analysis of legal and economic nature have devoted their research leading domestic and foreign scholars: V. M. Ermolenko, M. I. Kozir, P. F. Kulinich, A. V. Lisovyi, V. V. Nosik, A. I. Pavlov, A. M. Stativka, V. Y. Urkevych, M. V. Shulha and other scientists. Still open is very acute problem of legal support and overcoming gaps legislation on public relations for the revival of rural areas from the doldrums of their sustainable socio-economic and environmental development. Paper objective. Main objective of the article is based on structural analysis of the norms of existing national legislation and recent scientific literature relevant to clarify the theoretical and legal problems of rural areas in Ukraine, which will make it possible to develop recommendations to improve the agrarian regulations and other legislation. Paper main body. In economically developed countries implemented policies align economic development of the region to the center, and not vice versa, as the years have tried to implement in Ukraine on the principle of centralization of power. Thus the social constitutional state must act springboard for self regions. Legitimate definition of «rural area» and «depressed rural areas» in domestic legislation still exists. However, the science produced a large number of definitions, including rural and sustainable rural development. Depressed rural areas can be considered rural areas, where over the past three years, rural population density, rate of natural increase of population, the level of average wages and the volume of sales of agricultural products (works, services) per capita is much lower and the share of employment in agriculture sector is significantly higher than the corresponding average of the areas of this group. Conclusions of the research. Complex social relations in the field of sustainable development of rural areas as well as to revive the depressed rural areas are the elements of agrarian relations is the subject field of agrarian law in Ukraine. Such categories as «depressed rural areas» and «sustainable rural development» can not be an abstract object agro-regulation. These categories require legal consolidation of the Law of Ukraine of 24 June 2004 year № 1877-IV «About State Support of Agriculture of Ukraine». The first step of our country in the process of convergence State Agrarian Policy of Ukraine and the Common Agricultural Policy should be to increase accountability for violations in the agricultural sector because of abuse and criminal offenses in this area undermine the food security of Ukraine, and is further compounded by the economic crisis in the country, and put away the possibility Ukraine become a full member. To ensure the implementation of the priority areas of sustainable development of rural areas, it is advisable to use 4 main groups of instruments: 1) improving the legal framework of rural development at national, regional and local levels; 2) optimization of financial and fiscal relations with rural development at all levels; 3) improving the forms and methods of economic development of rural areas and finally; 4) improving the efficiency of the legislative and executive bodies at all levels and enterprises, organizations and institutions that ensure the sustainable development of rural areas.